Combustion studies of blended fuel oil as an alternative fuel for industrial gas turbines (AFTUR) and controlling NOx and soot emissions - Hussain, Ahmad; Ani, Farid Nasir; Mustafa, Azeman; Mamat, Zainul Asri; Zardi, Zulfadhly; Abdul Aziz, Abdul Aziz (2005)
cloba1 ifterest in clean power generation has driven continued improvement oi power systems. lmprovemeni eiforts focus on reducing emissions impfoving efficiency and lowering costs withoui sacrificing reliabillty. Advances arc occur ng on all three fronts, but prcgress s lslally achieved on a single-composition fuel. Thus, there is a need to consider iuel composiiion and fuel prcperty variables on advanced power genetaiion sysiems Cuffent gas turbine systems that are capabie of buming fuels arc normally developed for a slngle specific flel (such as naiural gas or domestic fuel oil) and use cofventional diffusion flame technology with relatively high levels of NOx and padially unbu.ned species em ssions